Evaluación de beauveria bassiana para el control del gorgojo barrenador del grano (pagiocerus frontalis), en grano almacenado de maíz (zea mays l.), bajo condiciones controladas, Salache – Latacunga – Cotopaxi - 2021. - Tituaña Peralta, José Israel (2022)
Present research evaluated Beauveria bassiana grain borer weevil control (Pagiocerus frontalis) at stored corn grains, under controlled conditions. It proposes an alternative to insect pest control that affects corn seeds, which farmers have opted only for use of gassing insecticides based on aluminum phosphide, which leaves phosphine residues that affect human health. The research consisted three phases, at first phase Beauveria bassiana strains were obtained, at second phase stock solution was obtained for its dosage and at third phase doses of Beauveria bassiana were applied on bioassays using a randomized complete block design (DBCA) with a factorial arrangement of AxBxC+1 (control), with three replications, where factor A corresponds to (native and commercial Beauveria), factor B corresponds to doses (2, 2.5 and 3 cc) and factor C corresponds to application form (Preventive and Curative). Under study variables were; mortality percentage, damaged grains and grain weight loss percentage. These variables were first normalized and then analyzed at InfoStat program and after obtaining statistically significant results on ADEVA, 5% Tukey test was applied to obtain different ranges of significance. It was determined that, for mortality (T3), corresponds to the application of native Beauveria with dose 3 (high) and preventive method application, recorded 100% mortality compared to the control (T13), which did not record any dead insects. With respect to damaged grains, it was determined that the best treatment is (T3), which corresponds to native Beauveria application with dose 3 (high) and preventive application form, which registered 26% damaged grains, being the lowest percentage compared to (T13) control, which registered 80% damaged grains. The last variable corresponding to grain weight loss was determined to be the best treatment (T3), which corresponds to native Beauveria application with dose 3 (high) and preventive application, which registered 29.9% weight loss, being the lowest percentage for this variable, compared to (T13) control, which presented the highest percentage of weight loss, reaching 85.2%.